Short- and Mid-Term Outcomes of Endovascular Stenting for the Treatment of Post-Thrombotic Syndrome due to Iliofemoral and Caval Occlusive Disease: A Multi-Centric Study from the French Society of Diagnostic and Interventional Cardiovascular Imaging (SFICV) - David, Arthur; Thony, Frédéric; del Giudice, Costantino; Goyault, Gilles; Loffroy, Romaric; Guillen, Kévin; Le Bras, Yann; Marcelin, Clément; Monnin-Bares, Valérie; Heautot, Jean-François; Lablee, Alexandre; Marek, Pierre; et al. (CardioVascular and Interventional Radiology, 2022)
Purpose To assess the results of endovascular treatment in a large population of patients suffering from post-thrombotic syndrome (PTS) due to iliocaval occlusive disease. Methods In this retrospective multi-center study, 698 patients treated by stenting for PTS in 15 French centers were analyzed. Primary, primary assisted, and secondary patency rates were assessed, and clinical efficacy was evaluated using Villalta and Chronic Venous Insufficiency Questionnaire in 20 questions (CIVIQ-20) scores. Outcomes were compared against pre-operative CT-based severity of the post-thrombotic lesions in the thigh (4 grades). Results Technical success, defined as successful recanalization and stent deployment restoring rapid anterograde flow in the targeted vessel, was obtained in 668 (95.7%) patients with a complication rate of 3.9%. After a mean follow-up of 21.0 months, primary patency, primary assisted patency, and secondary patency were achieved in 537 (80.4%), 566 (84.7%), and 616 (92.2%) of the 668 patients, respectively. Venous patency was strongly correlated to the grade of post-thrombotic changes in the thigh, with secondary patency rates of 96.0%, 92.9%, 88.4%, and 78.9%, respectively, for grades 0 to 3 ( p = .0008). The mean improvements of Villalta and CIVIQ-20 scores were 7.0 ± 4.7 points ( p < .0001) and 19.1 ± 14.8 points ( p < .0001), respectively. Conclusion Endovascular stenting as a treatment option for PTS due to chronic iliocaval venous occlusion generates a high technical success, low morbidity, high midterm patency rate, and clinical improvement. Venous patency was strongly correlated to the severity of post-thrombotic lesions in the thigh.